An electrically tunable metasurface integrated with graphene for mid-infrared light modulation - 王宗鹏;邓娅;孙连峰 (Chinese physics B, 2017)
We propose a low-cost plasmonic metasurface integrated with single-layer graphene for dynamic modulation of midinfrared light. The plasmonic metasurface is composed of an array of split magnetic resonators（MRs） where a nano slit is included. Extraordinary optical transmission（EOT） through the deep subwavelength slit is observed by excitation of magnetic plasmons in the split MRs. Furthermore, the introduction of the slit provides strongly enhanced fields around the graphene layer, leading to a large tuning effect on the EOT by changing the Fermi energy of the graphene. The proposed metasurface can be utilized as an optical modulator with a broad modulation width（15 μm） or an optical switch with a high on/off ratio（〉 100）. Meanwhile, the overall thickness of the metasurface is 430 nm, which is tens of times smaller than the operating wavelength. This work may have potential applications in mid-infrared optoelectrical devices and give insights into reconfigurable flat optics and optoelectronics.